Relationship between pathological findings and enzymes of the energy metabolism in liver of rats infected by Trypanosoma evansi - Baldissera M.D. (2015)
© 2015 Elsevier B.V.The aim of this study was to investigate the activities of important enzymes involved in the energetic metabolism in the liver of rats experimentally infected by Trypanosoma evansi. Adenylate kinase (AK), pyruvate kinase (PK), and lactate dehydrogenase (LDH) in liver homogenate, as well as aspartate aminotransferase (AST), alanine aminotransferase (ALT), and clotting time in plasma were evaluated at 5 and 15days post-infection (PI). The activities of the respiratory chain complexes and of Na+, K+-ATPase were also evaluated. This study demonstrates energetic metabolism impairment in rats infected by T. evansi. A reduced energy metabolism in the liver of rats infected by T. evansi was observed, demonstrated by AK decreased and PK increased activities at 5days PI, a mechanism known as energetic compensation. However, at 15days PI a decrease of AK and PK activities were observed. In addition, an increase in the activities of respiratory chain complexes II, II-III and IV in infected rats at 15days PI, and a decrease of Na+, K+-ATPase activities in infected rats on days 5 and 15 PI were verified. In the plasma, we observed an increase in ALT and AST activities on days 5 and 15 PI, and increase in clotting time in infected rats. The changes caused by T. evansi infection on the activity of enzymes of hepatic energy metabolism can corroborate to elucidate the mechanisms that lead to liver injury and inflammatory infiltration verified in T. evansi infected rats. Therefore, these alterations are directly related to disease pathogenesis.